2018
DOI: 10.1007/s41811-018-0027-8
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Therapy or Behavioral Activation for Major Depressive Disorder in Dutch Mental Health Care: Pilot Effectiveness and Process Trial

Abstract: Few studies have investigated the association between psychotherapeutic approaches and their processes in routine psychological practice. We compared cognitive therapy (CT) and behavioral activation (BA) on their effectiveness and change processes. Forty-three depressed patients participated in our trial. Scores on depression and specific and nonspecific factors were collected at seven time points and analyzed using RM-ANOVA and multiple linear regressions. No differences in depression reduction emerged betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…In the experimental phase of the research, it was concluded that BA-based A-BAP administration effectively reduced depressive symptoms in adolescents. This conclusion coincides with the finding that BA-based interventions to reduce depression in adolescents show effective results in various cultures (Hopko et al 2003aDimidjian et al 2006, Cuijpers et al 2007, Chu et al 2009, Collado et al 2014, McCauley et al 2016, Nyström et al 2017, Bolinski et al 2018, Pass et al 2018b. While the effectiveness of BA-based interventions for adolescent and adult depression is known, it has recently been proven to be an effective model in Figure 3.…”
Section: Discussionsupporting
confidence: 83%
“…In the experimental phase of the research, it was concluded that BA-based A-BAP administration effectively reduced depressive symptoms in adolescents. This conclusion coincides with the finding that BA-based interventions to reduce depression in adolescents show effective results in various cultures (Hopko et al 2003aDimidjian et al 2006, Cuijpers et al 2007, Chu et al 2009, Collado et al 2014, McCauley et al 2016, Nyström et al 2017, Bolinski et al 2018, Pass et al 2018b. While the effectiveness of BA-based interventions for adolescent and adult depression is known, it has recently been proven to be an effective model in Figure 3.…”
Section: Discussionsupporting
confidence: 83%
“…Depression is a common mental disorder and is associated with a substantial burden for patients and those around them [1-3]. Currently, pharmacotherapy, cognitive behavioural therapy, and interpersonal therapy are the most frequently used evidence-based psychological treatments for depression, but research suggests that behavioural activation (BA) is equally effective [4-9] while it is less costly and complex than other psychotherapies [10, 11].…”
Section: Introductionmentioning
confidence: 99%